PENINGKATAN KEAKTIFAN BELAJAR DENGAN STRATEGI QUESTION STUDENTS HAVE PADA MATA PELAJARAN MATEMATIKA KELAS VI.B SDN 14 SITIUNG - Irwandra Efendi (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2020)
This study aims to improve student learning activeness with the Question Studentst Have Model. This type of research is classroom action research with the research subjects being students of class VI.B SDN 14 Sitiung with a total of 20 students. The data in this study were collected using observation sheets. The data were processed using the percentage technique. Based on the results of observations of student learning activeness during the Teaching and Learning Process (PBM) in cycles I and II, it was seen that there was an increase in learning activeness of class VI.B SDN 14 Sitiung students. During the application of the Question Students Have Model, positive activeness increased by 11%; namely from 84% in cycle I to 97% in cycle II. Meanwhile, negative activeness decreased by 17%; namely from 20% in cycle I to 3% in cycle II. The increase in student learning activeness occurred due to the addition of actions in cycle II, namely ordering students to read teaching materials at home, giving rewards and punishments, and increasing student motivation by giving rewards to students who were serious and earnest in carrying out the teaching and learning process and giving punishment to students who violate.